KUALITAS HASIL BUSANA KERJA MENGGUNAKAN LINING KAIN ERRO DAN KAIN ASAHI - Sakdiyah, Fitrah; Wahyuningsih, Sri Endah; Ainul Hukma, Nabila Fitria (Fashion and Fashion Education Journal, 2021)
Abstract. The purposed of the research was to describe about the quality of work cloth with erro and asahi fabric lining. The method of the research was an experiment research with quantity data. The steps of this research were 1) product of work cloth , 2) fitting by experts, 3) data analysis, 4) result. Data collection methods in this research are observations, literature review, and observasion sheet . Data analysis techniques used descriptive percentage. The result of the product validation aspect got 82% (very good) and assesment of instrument got 84,4% (very good). The conclutions of this research was needed to describe of quality of work cloth with erro and asahi fabic lining. The quality of work cloth with erro got 92,88% (very comfortable) for the comfortable and asahi fabric got 74,88% (comfortable enough). The advice from this research is asahi fabric is less recommended for lining of work cloth. Keywords: asahi fabric; erro fabric; lining; work cloth Abstrak. Penelitian ini bertujuan mendeskribsikan kualitas hasil busana kerja menggunakan kain erro dan kain asahi. Metode penelitian ini eksperimen dengan data kuantitatif. Langkah penelitian antara lain 1) hasil produk busana kerja, 2) fitting oleh panelis, 3) analisis data, 4) hasil. Metode pengumpulan data yaitu observasi, studi pustaka, dan lembar pengamatan. Analisis data yang digunakan adalah descriptive persentase. Hasil validasi produk mendapat 82% (sangat baik) dan validasi instrument sebesar 84,4% (sangat baik). Kesimpulan dari penelitian ini untuk mendeskripsikan kualitas dari busana kerja dengan lining kain erro dan kain asahi. Kualitas dari busana kerja menggunakan kain erro untuk kenyamanan mendapat 92,88% (sangat nyaman) dan kain asahi 74,88% (cukup nyaman). Saran dari penelitian ini adalah kain asahi kurang dianjurkan sebagai lining busana kerja. Kata Kunci: Busana Kerja, Kain Asahi, Kain Erro, Pelapis